Workers in the Crowd: The Labour Market Impact of the Online Platform Economy - Michele Cantarella; Chiara Strozzi (Institute of Labor Economics (IZA), 2019)
In this paper, we compare wages and labor market conditions of individuals engaged in online platform work and in traditional occupations by exploiting individual-level survey data on crowdworkers belonging to the largest micro-task marketplaces, focusing on evidence from the United States and Europe. To match similar individuals, survey responses of crowdworkers from the US and EU have been harmonised with the American Working Conditions Survey (AWCS) and the European Working Conditions Survey (EWCS). Our findings indicate that traditional workers retain a significant premium in their earnings with respect to online platform workers, and that those differences are not affected by the observed and unobserved ability of individuals. This holds true also taking into account similar levels of routine intensity and abstractness in their jobs, as well as the time spent working. Moreover, labour force in crowdworking arrangements appears to suffer from high levels of under-utilisation, with crowdworkers being more likely to be left wanting for more work than comparable individuals.
Keywords: J31; J42; F66; 330; crowdwork; online platform economy; micro-tasks; routine intensity; labour market conditions